Developing a conceptual framework for business model innovation in the context of open innovation - Lingyun Wang; Jaring, P.; Arto Wallin (2009 3rd IEEE International Conference on Digital Ecosystems and Technologies, 2009)
This paper aims to understand business model in the context of open innovation, and to develop a conceptual framework for business model innovation in the process towards an open business model. The literature study presented in this paper shows that a business model in the context of open innovation is not a strategy of a company, but a cognitive tool and a mediating construct between technology innovation and economic value. By identifying the origins and possibilities of business model innovation based on related literature, this paper presents a conceptual framework for business model innovation in the context of open innovation. The framework helps companies to become aware of the elements required when heading toward an open business model. This paper serves as a starting point to learn the process of business model innovation.